Impact of a population‐based asthma management program in France (Sophia Asthme): A matched controlled before‐and‐after quasi‐experimental study using the French health insurance database (SNDS). Issue 8 (24th June 2019) - Dib, Fadia; de Rycke, Yann; Guillo, Sylvie; Lafourcade, Alexandre; Raherison, Chantal; Taillé, Camille; Tubach, Florence
Abstract: Purpose: Sophia Asthme (SA) is a chronic disease management program of the French national health insurance for adult patients with asthma. We evaluated the early impact of this intervention. Methods: We conducted a matched controlled, before‐and‐after quasi‐experimental study within the French Health Insurance Database ( Système National Des Données de Santé [SNDS]). The SA program was implemented in a set of 18 Départements in France and targeted 18‐ to 44‐year‐old subjects, with at least two reimbursement dates for asthma drug therapy during the 12‐month period prior to program targeting. Change in outcomes was assessed from the "before program" period (January‐December 2014) to the "after program implementation" period (March 2015‐February 2016) in the program group (eligible to SA program in the 18 Départements ) and in the matched controlled group. The main outcome measure was the before‐after change in proportion of subjects with a controllers/(controllers+relievers) ratio greater than 50%. Results: Of the 99 578 subjects of the program group, 9225 (9.3%) actually participated in SA program. The program had no significant impact on the proportion of subjects with a ratio greater than 50%. However, subjects exposed to SA program were significantly more likely to be dispensed controller medications (OR = 1.04; 95% CI, 1.01‐1.07) and to sustain their use of these medications (OR = 1.08; 95% CI, 1.05‐1.12). Conclusion: We did not demonstrate any significant impact of the program on the primary outcome. The modest yet encouraging findings of this early evaluation suggest the need for reformulation of the program and its evaluation.